Produção de curtas metragens como recurso para educação inclusiva - Venturini, Aline Dal Bem (2017)
The present research entitled "Production of Short Films as a Resource for Inclusive Education" developed in the research line Development of Educational Technologies in Network and in the area of concentration Educational Technologies in Network for Innovation and Democratization of Education in the Master course in Educational Technologies In Network at UFSM, focuses on the production of two short films produced by students with intellectual disabilities from a state school in the interior of Santa Maria-RS. Inclusion in school presupposes beyond the right to the vacancy in a regular educational institution. It includes aid in the teaching-learning process and the right of the student to count on different pedagogical alternatives, according to their specifics, making him / her a subject in the construction of knowledge. Given this, it is believed that the school, by providing students with conditions for production and interaction with pedagogical and technological resources, allows students to stimulate creativity and affectivity, as well as facilitates the constitution of identities capable of withstanding restlessness, welcoming and coexisting with Diversity. In this scenario, the present research carried out a study on the technological resource short film, seeking to analyze the feasibility of the same as a subsidy to the adaptive and inclusive process of students with intellectual disabilities. It is a qualitative study based on the presuppositions of participatory action research. Participants in the action research were students with intellectual disabilities, students and teachers. From the exploration of reality, together with the students, the planning, development and evaluation of the action was operationalized. After the production of the short films, a semi-structured interview was conducted with students with intellectual disabilities in order to know their perceptions about participating in the short film. The participation of students with intellectual disabilities as protagonists in the production of the short films reflected in perceptions of reception, inclusion and appreciation.